Nonverbal behavior and the vertical dimension of social relations a meta-analysis. [article]. - Hall,J. A.
The vertical dimension of interpersonal relations (relating to dominance, power, and status) was examined in association with nonverbal behaviors that included facial behavior, gaze, interpersonal distance, body movement, touch, vocal behaviors, posed encoding skill, and others. Results were separately summarized for people's beliefs (perceptions) about the relation of verticality to nonverbal behavior and for actual relations between verticality and nonverbal behavior. Beliefs/perceptions were stronger and much more prevalent than were actual verticality effects. Perceived and actual relations were positively correlated across behaviors. Heterogeneity was great, suggesting that verticality is not a psychologically uniform construct in regard to nonverbal behavior. Finally, comparison of the verticality effects to those that have been documented for gender in relation to nonverbal behavior revealed only a limited degree of parallelism. -- (from the author)